The Steptoean Positive Carbon Isotope Excursion (SPICE), inorganic aragonite precipitation and sea water chemistry: Insights from the Middle–Late Cambrian Port au Port Group, Newfoundland. (12th November 2021) - Neilson, Joyce E.; Barili, Rosalia; Brasier, Alexander; De Ros, Luiz F.; Ledingham, Sarah
Abstract: The Late Cambrian Steptoean Positive Carbon Isotope Excursion marks a time of significant change in ocean chemistry and trilobite faunas. On the lead up to the carbon isotope excursion and at the excursion itself, there is global evidence from Laurentia and Gondwana of cementation by primary aragonite in shallow subtidal environments accompanied by deposition of aragonitic ooids. However, this occurred at a time widely considered to have been characterised by 'calcite seas' when the primary inorganic phases (marine cements and ooids) are normally presumed calcitic. This study has investigated the chemostratigraphy of the Middle–Late Cambrian Port au Port Group, Newfoundland, including the early marine cements. Here, the marine cements contain increasing concentrations of strontium towards the peak carbon isotope excursion (up to 5500 ppm at the peak excursion) before dropping off post‐peak excursion, consistent with the original cements having been aragonitic. This trend is accompanied by relict oomouldic porosity, again suggesting an aragonitic precursor. Primary inorganic mineralogy is largely controlled by the Mg/Ca ratio of sea water but estimates of the Mg/Ca ratio of Late Cambrian oceans are variable (0.8–2). At this level, other factors such as water temperature and pCO2 have been shown to affect mineralogy with warm waters and high levels of CO2 favouring aragonite. It is possible that the warm waters and anoxia that caused the carbon isotope excursion created conditions favourable for the precipitation of aragonite at the same time as major trilobite faunal turnover. Abstract : In a study of the Middle–Late Cambrian Port au Port Group, Newfoundland, marine cements precipitated on the lead up to and around the Steptoean Positive Carbon Isotope Excursion (SPICE) have been shown to contain increasing levels of strontium (up to 5500 ppm). Although this is a period characterised by calcite seas, it is suggested that at a Mg/Ca ratio of 0.8–2, high water temperatures and increased pCO2, inorganic aragonite in the form of marine cements and ooids, could have precipitated.